Orientation and Formulation of Islamic Education Philosophy Learning Materials in Higher Education in the Context of The Disruption Era - Dawi, Muhammad Nuh; Harahap, Ahmad Sukri (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze the formulation of educational philosophy learning materials in Islamic religious tertiary institutions in the context of disruption. This research focuses on two things, namely, the learning orientation of educational philosophy and the formulation of Islamic educational philosophy material in the context of the era of disruption. The research was conducted at the STAI Serdang Lubuk Pakam and was carried out for six months. This study uses qualitative research methods using narrative studies. The data sources for this research consisted of informants in the study, namely Islamic education philosophy lecturers, documents, namely lecturer material and learning plans, and library sources from previous research results. The study results reveal that the learning orientation of Islamic education philosophy is to provide students with the ability to understand the essence of Islamic education by studying the philosophical concepts of Islamic teachings originating from the Al-Qura'n and Hadith. The formulation in the context of the era of disruption is related to the essence of humans, nature, educators, students, curriculum, methods and evaluations that are adapted to the needs of modern society. Namely forming graduates who have deep thoughts and can analyze various elements or components related to Islamic education critically.